Macakurzin C Derivatives as a Novel Pharmacophore for Pan-Peroxisome Proliferator-Activated Receptor Modulator - Ko, Hyejin; An, Seungchan; Jang, Hongjun; Ahn, Sungjin; Park, In Guk; Hwang, Seok Young; Gong, Junpyo; Oh, Soyeon; Kwak, Soo Yeon; Choi, Won Jun; Kim, Hyoungsu; Noh, Minsoo (Biomolecules and Therapeutics, 2023)
The natural flavonoid macakurzin C (1) exhibited adiponectin biosynthesis-inducing activity during adipogenesis in human bone marrow mesenchymal stem cells and its molecular mechanism was directly associated with a pan-peroxisome proliferator-activat-ed receptor (PPAR) modulator affecting all three PPAR subtypes α, γ, and δ. In this study, increases in adiponectin biosynthesis-inducing activity by macakurzin C derivatives (2–7) were studied. The most potent adiponectin biosynthesis-inducing compound 6, macakurzin C 3,5-dimethylether, was elucidated as a dual PPARα/γ modulator. Compound 6 may exhibit the most potent activity because of the antagonistic relationship between PPARδ and PPARγ. Docking studies revealed that the O-methylation of macakurzin C to generate compound 6 significantly disrupted PPARδ binding. Compound 6 has therapeutic potential in hypoadi-ponectinemia-related metabolic diseases.
Keywords: Adiponectin; Human bone marrow mesenchymal stem cells; Macakurzin C derivative; Peroxisome proliferator-activated receptor; PPARα/γ dual modulator